Heterolayered films of monolayer WS₂ nanosheets on monolayer graphene embedded in poly(methyl methacrylate) for plasmonic biosensing - Das, Chandreyee Manas (2021)
The interplay between light photons and nanomaterials can give rise to many striking phenomena. Surface plasmon resonance (SPR), which is one such plasmonic sensing mechanism, is gaining much attention from the biomedical fraternity. Two-dimensional (2D) nanomaterials like transition-metal dichalcogenides (TMDCs) and graphenes are recently discovered nanomaterials that have favorable properties like high optical absorption. These materials have been applied extensively in the fields of drug delivery and cancer therapy. However, their applications in the area of plasmonic biosensing need to be explored more. Hence, using commercial SPR sensors, we demonstrate the effectiveness of heterostructured monolayer nanosheets of graphene and WS2 for a plasmonic-based detection system of a specific ligand.analyte interaction between bovine serum albumin (BSA) and anti- BSA. Our detection technique does not require any complex functionalization scheme as the graphene.WS2 nanosheet-coated gold chip can attach protein molecules through hydrophobic interactions. The limit of detection (LOD) obtained for the anti-BSA protein is 0.44 μg/mL.